2004
DOI: 10.1159/000080948
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Melanoma Metastatic to the Retina and Vitreous

Abstract: Purpose: Report of a case of retinal and vitreous metastases of a systemic melanoma, possibly arising in the lung, that responded favourably to radiotherapy. Case Report: Retinal and vitreous metastases were demonstrated in a 57-year-old woman during routine follow-up after surgical resection of a melanoma presumed to be a primary pulmonary melanoma. After a 7-week observation period, which confirmed the progressive nature of the intra-ocular lesions, the patient was treated by external beam radiotherapy at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 42 publications
0
16
0
3
Order By: Relevance
“…In our study, the neovascular glaucoma rate was 20%, which was not higher than reported in the literature for uveal melanoma in general. As mentioned above, exudative retinal detachment is a risk factor for neovascular glaucoma, which is the leading cause for enucleation [2,4,10,11,12,13]. Therefore, it would be interesting to perform VEGF measurements before and after vitrectomy to show that perhaps by reattachment of the retina, levels of VEGF are lowered to the same levels as in uveal melanoma in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the neovascular glaucoma rate was 20%, which was not higher than reported in the literature for uveal melanoma in general. As mentioned above, exudative retinal detachment is a risk factor for neovascular glaucoma, which is the leading cause for enucleation [2,4,10,11,12,13]. Therefore, it would be interesting to perform VEGF measurements before and after vitrectomy to show that perhaps by reattachment of the retina, levels of VEGF are lowered to the same levels as in uveal melanoma in general.…”
Section: Discussionmentioning
confidence: 99%
“…Functional outcomes depend inversely on the lag duration between retinal detachment and reattachment. Furthermore, exudative retinal detachment is a risk factor for neovascular glaucoma possibly leading to enucleation with no influence on survival rates [2,4,10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous melanoma metastatic to the eye commonly involves the choroid (75% of cases) or the retina (20% of cases) with isolated vitreous metastasis being rare (4% of cases) [1,2,3,4,5]. The mechanisms and the route through which cutaneous melanoma cells metastasize to the eye are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Cases involving the choroid or the retina usually present with loss of visual acuity or visual field defects [5]. Vitreous metastases commonly present with floaters and loss of visual acuity [4]. Pain and inflammation are a late sign of ocular metastases and commonly occur as a result of neovascular glaucoma [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation